2020
DOI: 10.1093/ehjacc/zuaa031
|View full text |Cite
|
Sign up to set email alerts
|

Left Impella®-device as bridge from cardiogenic shock with acute, severe mitral regurgitation to MitraClip®-procedure: a new option for critically ill patients

Abstract: Aims Patients presenting with cardiogenic shock (CS) related to acute, severe mitral regurgitation (MR) are often considered too ill for immediate surgical intervention. Therefore, other less invasive techniques for haemodynamic stabilization should be explored. The purpose of this exploratory study was to investigate the feasibility and outcomes in patients with CS due to severe MR by using a novel approach combining haemodynamic stabilization with left Impella-support plus MR-reduction usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…Baseline hemodynamics in patients with trace/mild FMR were not significantly different from patients with moderate and moderate-tosevere/severe FMR. At 24 hours post-Impella implant, there was a significant decrease in CVP (12 [8-14] to 9 [7][8][9][10][11], p ¼ 0.012), a significant decrease in pulmonary artery diastolic pressure (PADP; 25 [19][20][21][22][23][24][25][26][27] to 18 [14-21], p ¼ 0.002) and pulmonary capillary wedge pressure (22 [16][17][18][19][20][21][22][23][24][25][26] to 17 [10][11][12][13][14][15][16][17][18][19][20], p ¼ 0.008), a significant drop in systemic vascular resistance (1541 [1225-1914] to 960 [864-1183], p 0.001), a significant decrease in serum lactate levels (1.9 [1.2-2.7] to 1.3 [1-1.7], p ¼ 0.046), and a significant decrease in vasoactive-inotrope score (VIS; 12 [7][8][9][10][11][12][13][14][15][16][17][18]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline hemodynamics in patients with trace/mild FMR were not significantly different from patients with moderate and moderate-tosevere/severe FMR. At 24 hours post-Impella implant, there was a significant decrease in CVP (12 [8-14] to 9 [7][8][9][10][11], p ¼ 0.012), a significant decrease in pulmonary artery diastolic pressure (PADP; 25 [19][20][21][22][23][24][25][26][27] to 18 [14-21], p ¼ 0.002) and pulmonary capillary wedge pressure (22 [16][17][18][19][20][21][22][23][24][25][26] to 17 [10][11][12][13][14][15][16][17][18][19][20], p ¼ 0.008), a significant drop in systemic vascular resistance (1541 [1225-1914] to 960 [864-1183], p 0.001), a significant decrease in serum lactate levels (1.9 [1.2-2.7] to 1.3 [1-1.7], p ¼ 0.046), and a significant decrease in vasoactive-inotrope score (VIS; 12 [7][8][9][10][11][12][13][14][15][16][17][18]…”
Section: Resultsmentioning
confidence: 99%
“…This study also found that neither baseline nor residual MR affected survival at 24 months post-LVAD implant. 13 The Impella 5.5 can provide flows comparable to durable LVADs, but only small case series have examined the use of Impella in the setting of CS with concomitant severe MR. 9,10 In our small, retrospective cohort, we make 3 important observations: (1) the Impella 5.5 did not appear to acutely (within 24 hours) ameliorate moderate or greater FMR; (2) Impella 5.5 did provide significant left ventricular unloading as evidenced by a reduction in intracardiac filling pressures and lactate clearance as well as a significant decrease in systemic vascular resistance and vasoactive-inotrope score (Table 1); and (3) a significant proportion of patients in our cohort (42%) experienced NHR on Impella 5.5 support, regardless of baseline/residual FMR severity (Figure 1). These observations were made across the entire cohort, regardless of baseline severity of FMR.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that significant MR before Impella weaning was related to outcomes after Impella weaning. These patients could be considered for additional interventions, such as surgical or edge‐to‐edge mitral valve repair, prior to Impella weaning 24–26 . Our study included three cases that supported this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Of four patients who were weaned Impella because of complications, three patients with intracranial hemorrhage had PAWP 17 mm Hg [IQR 8-20], MPAP 25 mm Hg [23][24][25][26], and CPO 0.61 Watts [0.55-0.65], one patient with limb ischemia had PAWP 15 mm Hg, MPAP 23 mm Hg, and CPO 0.61 Watts before weaning. Four non-survival patients with bleeding events as causes of deaths after Impella weaning had PAWP 18 mm Hg [10][11][12][13][14][15][16][17][18][19][20][21], MPAP 25 mm Hg [23][24][25][26], and CPO 0.58 Watts [0.43-0.64] before weaning.…”
Section: Hemodynamic Factorsmentioning
confidence: 99%
“…Extremely rare applications, such as Impella-facilitated edge-to-edge mitral valve repair, are beyond the scope of this review. 67 A final section discusses Impella-associated complications.…”
mentioning
confidence: 99%